Evaluation of Water Resources Carrying Capacity in Henan Province Basedon Entropy-weight Fuzzy Comprehensive Evaluation Model - CHEN Haitao; XU Jiahao (Renmin Zhujiang)
According to the actual situation of water resources in Henan Province, this paperselects 13 evaluation indexes from water resources, social economy and ecological environment tobuild the evaluation indexes system of water resources carrying system in Henan Province, andevaluates the water resources carrying capacity in Henan Province in recent ten years based on theentropy-weight fuzzy comprehensive evaluation model. The results show that the overall developmenttrend of water resources carrying capacity in Henan Province is upward, and the water resourcescarrying capacity in 2015—2017 is significantly improved compared with that before 2015. Thedevelopment and utilization of water resources in Henan Province has reached a certain scale,which can meet the needs of social economy and ecological protection, but the development space issmall. Therefore, it is necessary to optimize the water resources allocation, and realize thescientific and efficient development and utilization of water resources to ensure the steadydevelopment of social economy in Henan Province. The research results of this paper have certainreference value for realizing the sustainable development of water resources in Henan Province.